2020
DOI: 10.1063/5.0012544
|View full text |Cite
|
Sign up to set email alerts
|

Flow-structure interactions of two tandem inverted flags in a water tunnel

Abstract: The dynamic behaviors and vortex interaction modes of two tandem inverted flags at different gap distances and flow velocities are investigated experimentally in this paper. The results show that the straight, flapping, and deflected modes can still be observed with a successive increase in the flow velocity. The fixed-phase, different-frequency, changing-phase, alternating-phase, and aperiodic flapping modes are further found in the flapping mode. Considering the fixed phase difference and predominance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Recently, the concurrent operation of two or more inverted flags has started to gain attention, with two main configurations being considered: side-by-side (see Figure 1 b) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and tandem (see Figure 1 b) [ 51 , 52 , 53 ] configurations within the horizontal plane. Huertas-Cerdeira et al [ 45 ] experimentally studied the dynamic response of side-by-side inverted flags, with a transverse distance larger than double the length of the flag, demonstrating that the maximum angular amplitude is 36% higher than that of a single flag.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the concurrent operation of two or more inverted flags has started to gain attention, with two main configurations being considered: side-by-side (see Figure 1 b) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and tandem (see Figure 1 b) [ 51 , 52 , 53 ] configurations within the horizontal plane. Huertas-Cerdeira et al [ 45 ] experimentally studied the dynamic response of side-by-side inverted flags, with a transverse distance larger than double the length of the flag, demonstrating that the maximum angular amplitude is 36% higher than that of a single flag.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Huang et al [ 52 ] investigated the tandem configuration and found through numerical simulations that a destructive vortex merging reduces the flapping amplitude of the downstream inverted flag by 50% compared to a single flag. However, using an experimental approach, Hu et al [ 53 ] demonstrated that the downstream inverted flag can extract energy from the trailing edge vortex of the upstream flag at a critical flow velocity and a short streamwise distance, leading to increased angular amplitude of the downstream flag. This finding was found to be consistent with the behavior of tandem conventional flags observed by Jia and Yin [ 54 ] and Ristroph and Zhang [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four-wings model or Model B (Figures 1b 2b 3b) exploits an wing-wing interaction phenomenon named 'clap-and-peel' for generating thrust. There has been a surge of interest in the recent years to study the interaction of multiple bodies in a fluid flow [25] [26] [27]. Deb et al(2020) [26] observed in-phase and out-of-phase oscillations in a couple of rigid plates which are oriented one beside another, through wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%
“…1 b, 2 b, 3 b) exploits a wing-wing interaction phenomenon named ’clap-and-peel’ for generating thrust. There has been a surge of interest in recent years to study the interaction of multiple bodies in a fluid flow 27 – 29 . Deb et al 28 observed in-phase and out-of-phase oscillations in a couple of rigid plates which are oriented one beside the other, through wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%